2013
DOI: 10.1103/physreva.88.053418
|View full text |Cite
|
Sign up to set email alerts
|

Interference structures in photoelectron spectra of atoms ionized by XUV pulses in the presence of a strong IR field

Abstract: The dynamics of photoelectrons ionized by XUV pulses in the presence of a strong infrared (IR) field is theoretically investigated by solving the time-dependent Schrödinger equation (TDSE). We study the ionization dynamics of He by an XUV pulse in the presence of a relatively strong IR laser field, which is different from the conventional attosecond streaking experiments where a rather weak IR field is applied. Comparing with the photoelectron spectra produced by the IR field only, we find the spectra ionized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…For the latter, the interfering electron trajectories within the same optical cycle give rise to a well-determined modulation pattern encoding information of the ionization process in the subfemtosecond time scale. A similar behavior has been observed by J-W. Geng et al in [21] for single ionization of He by considering two XUV attosecond pulses separated by the duration of the laser cycle period. In the experiments the intensity of the NIR field varies across the laser focus leading to "washing out" of the interference features, which are very sensitive to the field strength [22].…”
Section: Introductionsupporting
confidence: 84%
“…For the latter, the interfering electron trajectories within the same optical cycle give rise to a well-determined modulation pattern encoding information of the ionization process in the subfemtosecond time scale. A similar behavior has been observed by J-W. Geng et al in [21] for single ionization of He by considering two XUV attosecond pulses separated by the duration of the laser cycle period. In the experiments the intensity of the NIR field varies across the laser focus leading to "washing out" of the interference features, which are very sensitive to the field strength [22].…”
Section: Introductionsupporting
confidence: 84%
“…Moreover, the rescattering process of atom in XUV+IR two-color laser fields has been attracted extensive attentions in recent years. It was found the interference structures, resulting from the interference between multiple collisions and directly ionized electrons [45][46][47]. Also it is demonstrated that when the recolliding electrons of the IR field revisit the parent ion, they can absorb an XUV photon, yielding high-energy electrons [48].…”
Section: Introductionmentioning
confidence: 99%
“…When the IR intensity is strong, it can cause significant electron ionization. Hence, the rescattering electron can absorb an XUV photon when it revisits the core [23] or can interfere with photoelectron of one XUV-photon ionization streaked by the strong IR field [24,25], which needs other theoretical models to be investigated and is beyond the scope of the present work.…”
Section: Introductionmentioning
confidence: 99%